Increased ambulatory arterial stiffness index correlated with monocyte chemoattractant protein-1 in prehypertensives. (12th October 2011) - Liu, Zhendong; Lu, Fanghong; Dong, Yuanli; Wang, Shujian; Zhao, Yingxin; Sun, Shangwen; Pan, Hui
Abstract : Objective: To investigate increased ambulatory arterial stiffness index correlated with plasma level and expression of monocyte chemoattractant protein-1. Methods: One hundred and eight subjects with prehypertension and 101 optimal normotensive subjects were eligible enrolled. Non-invasive ambulatory blood pressure monitoring was performed using automatic devices (TM-2421 and TM-2430; A&D, Tokyo, Japan) and ambulatory arterial stiffness index was calculated in all participants. Monocyte chemoattractant protein-1 expression was conducted by quantitative real-time reverse transcription-PCR (RT-PCR). Results: Ambulatory arterial stiffness index was 0.48±0.10% in prehypertensives, higher than that in optimism normotensives (t value=10.689, P-1 in prehypertensives.